Drug targeting hepatocytes specifically Asialoglycoprotein receptors - Rizvi, Ali Abbas; Ansari, Vaseem Ahamad; Mahmood, Tarique; Shariq, Mohammad (Journal of Neonatal Surgery, 2025)
The Asialoglycoprotein receptor has been on interest to target the liver for treatment of multiple ailments. Asialoglycoprotein receptors being easy target for carbohydrate molecules, contains a calcium ion channel, type C-lectins and are major on the hepatocyte (the outer covering of liver plasma membrane). This receptor has a great potential, it can help target a drug onto a specific liver site, it can be used for diagnostic and therapeutic purposes. When we discuss about liver diseases with a very minimal amount of nontargeting drug or a delivery system, is due to the high specificity, effective internalisation rate and also easy access to the blood and lymph vascular system. But then the targeting is not achieved as the drug can be carry forward with the flow of blood. We in this review article draw a conclusive structure of the number of molecules which can impact on targeting liver. Along with its use in liver diagnostics, it also examines the receptor's clinical importance in a variety of liver diseases. Graphical abstract Liver with hepatocyte cell on the surface containing ASGPR Figure 1: Different procedurs or ligands to target Asialoglycoprotein receptor